When Failure is the Only Option: How Communicative Framing Resources Organizational Innovation. (July 2023) - Smith, William Roth; Treem, Jeff; Love, Brad
Innovation is valuable for organizational success, yet it presents contradictions for workers who must choose between pursuing novel courses of action or practicing established strategy. One challenge is that many efforts at innovation are not successful, making workers reluctant to pursue novel projects. In this study, we seek to answer the question: How do individuals responsible for facilitating innovation in organizations communicatively construct and frame failure? Abductive analysis of interviews with 36 professionals in innovation-related roles reveal that these workers communicate in a way that frames the idea of failure in a way that bolsters innovation efforts. This framing is enacted through a variety of language tools, a mindset aligned with the frame, and the development of organizational strategy that communicatively supports this framing. The article argues that innovation failure is resourced via communicative framing as an asset that aids organizational learning. Overall, findings indicate that communication plays a central role in constituting innovation practices and facilitating change in organizations.